Nutrition transitions Diet and disease in the developing world - Popkin,Barry.M; Jacobs, David R. (Ed); Wilson, Ted (Ed); Caballero,Benjamin (Amsterdam # New Jersey Humana Press # Academic Press, 2006)
Nutritional epidemiology